Are patents the future evaluation documents for universities? - López-Borrull, Alexandre; Ortoll, Eva (Anuario ThinkEPI, 2012)
As technological documents of high value, patents are not only sources of information but can also be used to evaluate the quality of universities and their faculty. With the increasing number of patents by universities, it becomes necessary to create standard indicators
Keywords: Patents; Evaluation; Quality; Citations.